2020
DOI: 10.1016/j.scitotenv.2020.138813
|View full text |Cite
|
Sign up to set email alerts
|

Indirect effects of COVID-19 on the environment

Abstract: This research aims to show the positive and negative indirect effects of COVID-19 on the environment, particularly in the most affected countries such as China, USA, Italy, and Spain. Our research shows that there is a significant association between contingency measures and improvement in air quality, clean beaches and environmental noise reduction. On the other hand, there are also negative secondary aspects such as the reduction in recycling and the increase in waste, further endangering the contamination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
929
4
24

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,074 publications
(1,058 citation statements)
references
References 13 publications
27
929
4
24
Order By: Relevance
“…This had a positive impact on the environment, with pollution levels falling signi cantly in most cities of India (Mahato et al 2020;Sharma et al 2020). The same trends were reported in many other countries of the world, such as China (Bao and Zhang 2020;Muhammad et al 2020;Wang et al 2020b;Zambrano-monserrate et al 2020;),…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…This had a positive impact on the environment, with pollution levels falling signi cantly in most cities of India (Mahato et al 2020;Sharma et al 2020). The same trends were reported in many other countries of the world, such as China (Bao and Zhang 2020;Muhammad et al 2020;Wang et al 2020b;Zambrano-monserrate et al 2020;),…”
Section: Introductionsupporting
confidence: 59%
“…Italy (Cristina et al 2020;Muhammad et al 2020;Zambrano-monserrate et al 2020), Spain, France (Muhammad et al 2020;Zambrano-monserrate et al 2020), USA (Muhammad et al 2020), Germany (Zambrano-monserrate et al 2020), Brazil (Dantas et al 2020), Kazakhstan (Kerimray et al 2020), etc.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several unexpected environmental impacts that might have dire consequences on beachgoer safety and entire beach tourism destinations. The sudden desertion of tourist beaches has had a short-term positive environmental impact on coastal environments that have had time to recover from human pressures [ 55 , 56 , 57 ]. The resulting visual and acoustic qualities of undisturbed coasts have been noted in the media (see, for example, [ 58 , 59 ]) and by early empirical research papers that confirmed these observations [ 57 ].…”
Section: Environmental Considerationsmentioning
confidence: 99%
“…The coronavirus disease (COVID-19) pandemic has emerged as both a global health and socioeconomic crisis, with many countries implementing unparalleled mobility restrictions to control the spread of the virus. This unprecedented event, which has been referred to as the "anthropause", a period of reduced human mobility 1 , has led to sudden and often dramatic reductions in transport, energy consumption and consumer demand resulting in significant changes in the scale and extent of human stressors and their associated impacts on the natural environment [2][3][4][5][6] . To better understand the potential effects on the environment and biodiversity, there is an urgent need to quantify the magnitude and patterns of the changes in human activities.…”
Section: Introductionmentioning
confidence: 99%